THE IMPLEMENTATION OF GUESSING GAME TO INCREASE VOCABULARY OF THE GRADE EIGHT STUDENTS AT SMP NEGERI 1 SOJOL UTARA - Sari, Sri Wahyuni; Munir, Syahrul; Maf’ulah, Maf’ulah (e-Journal of ELTS (English Language Teaching Society), 2024)
The aim of this research is to find out whether the implementation of guessing game increases the vocabulary of the grade eight students at SMP Negeri 1 Sojol Utara or not. The research design was quantitative research. The researcher used total sampling techniques to select 36 students as samples for this research. The data were analyzed by using t-test. Based on the data analysis tests, the mean score in the experimental group's pre-test was 52.86 and the control group's mean score is 65.11. After doing the treatment, the students’ mean score of experimental group’s post-test was 85.56, greater than the control group's means score which is 80.44. The comparison of the test of scale describes that t-counted value= 4.35> t-table value= 2.01. Therefore, Ha is confirmed and Ho is rejected. It can be concluded that the implementation of guessing game increases the vocabulary of the grade eight students at SMP Negeri 1 Sojol Utara.